Apartment Living and Community Care: Experiences of People With Intellectual Disability, Their Families, and Support Staff - Carnemolla, Phillippa (2022)
Understanding how the design of urban infrastructure influences the independence and autonomy of people with intellectual disability has far-reaching implications for community inclusion and participation. This article explores how urban design elements of an apartment complex influence how a person with an intellectual disability receives support and participates in the wider community. The study reports on the post-occupancy evaluation of an Australian development of over 400 apartments in Sydney, where 25 people with intellectual disability received 24-hour support. Fifty-three interviews were conducted with people with intellectual disability, their families, and disability support staff. Participants with intellectual disability described what living in their new apartment was like and appreciated the outdoor gardens. However, they also explained that wayfinding was more difficult than in their previous homes—all free-standing group homes. Disability support staff discussed how providing community care for people with intellectual disability in an apartment differed from a suburban free-standing house. Findings were translated into design suggestions for improving service provision to people with disability through the urban design around multi-tower sites of mixed-tenure apartments. The article concludes with recommendations for urban design features to support safe, efficient, and quality care in a high-density urban setting. When viewed through a lens of social infrastructure, the results show how urban design has the potential to influence the collective independence and provision of care to diverse communities in urban centres and cities and is relevant to people with disability, older people, and other community groups who rely on community-care support to remain living independently at home.